ARBUSCULAR MYCORRHIZAL FUNGAL COMMUNITIES IN PASTURE AND TROPICAL RIPARIAN FOREST ECOSYSTEMS IN GUAJARÁ-MIRIM, RONDÔNIA, BRAZIL - Jesus, Jéssica Archanjelo; Caproni, Ana Lucy; Silva, Cristiane Figueira; Pereira, Marcos Gervasio; Santos, Otavio Augusto Queiroz; Berbara, Ricardo Luiz Louro (Floresta, 2021)
Understanding the dynamics of soil organisms in natural environments can be very useful for determining the quality of forest and agricultural ecosystems. This study aimed to assess arbuscular mycorrhizal fungal (AMF) communities in pasture and regenerating riparian forest sites in Guajará-Mirim, Rondônia, Brazil. Ten soil samples were randomly collected from each ecosystem in three seasons (2018 dry and rainy seasons and 2019 dry season). AMF species richness, frequency, spore density, Shannon–Wiener diversity index, Simpson’s dominance index, and ideal sample size were determined. Species richness varied among sites and seasons, with a tendency toward higher richness in pasture soil in the 2018 dry season. The dominant AMF species in both ecosystems were Glomus macrocarpum and Acaulospora mellea. The pasture site in the 2018 dry season had higher AMF diversity than the riparian forest in the 2018 rainy season and the 2019 dry season. The complete linkage distance between the pasture site in the 2019 dry season and all other sites/seasons was 100%. More than 10 soil samples are needed to accurately determine the richness of AMF species in pasture and riparian forest sites in Guajará-Mirim, Brazil.